Paula - Allende, Isabel (New York : HarperCollins Publishers, 1996)
Presents the story of Allende's ancestors and youth as it was written by her daughter's hospital bedside, reflecting the challenges and achievements of one family during a turbulent time in Chilean history.
Keywords: ISABEL ALLENDE FAMILY -- AUTOBIOGRAPHIES